An environment-friendly Fe3O4@CFAS porous ceramic: Adsorption of Cu(II) ions and process optimisation using response surface methodology. Issue 6 (15th March 2021) - Zhang, Jiayu; Yan, Mingwei; Sun, Guangchao; Liu, Kaiqi
Abstract: In this work, Fe3 O4 @CFAS composites for the adsorption of Cu(II) ions were successfully prepared using magnetic Fe3 O4 nanoparticles (MNPs) generated in situ on a coal fly ash-based porous ceramic support (CFAS) with high porosity. Response surface methodology (RSM) was employed to achieve the best conditions for the adsorption of Cu(II) ions. The results showed that the porosity of CFAS with a multi-stage pore structure was 75.79%. Compared with CFAS, Fe3 O4 @CFAS exhibited significant improvement in hydrophilicity without considerable variation in water permeation flux. The Cu(II) ion removal rate of Fe3 O4 @CFAS reached 94.89%, as determined using RSM. Given its good performance in water filtration and Cu(II) ion adsorption, Fe3 O4 @CFAS can be applied as an environment-friendly industrial wastewater treatment material.